JUSTIFICATION OF DESIGN PARAMETERS PERTAINING TO ELECTRIC HYDRAULIC CONTROLLER OF SUSPENSION - E. Ya. Strok; L. D. Belchik; T. L. Aleksandrova; S. L. Goravsky (Наука и техника)
The paper proposes a new approach to selection of rational design parameters for drop circuit of electric hydraulic controller which is based on mathematical modeling and computational experiment planning. The calculation results illustrate limits for speed of the suspension drop in respect of working elements of various weight in accordance with operational standards.